Tobacco earnings up in smoke - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Tobacco prices have been taking quite a drubbing from the success of anti-smoking campaigns in the North. During 2000, they sank to their lowest level in a decade, causing great concern among African growers. Until recently tobacco had been a...